USING AL-QURAN AS THE MEDIA IN TEACHING (FINDING) NOUNS AND NOUN PHRASE - YUSNI SINAGA M.HUM (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Islam is one of the international religion because the followers can be found most of in every country in the world, so Al-quran is the holy book (kibatulloh) of the Islam so Al-quran is the one of the internation religion. Al-quran stated by Alloh swt in Arabic language, Al-quran contents all found in world means all things in the universe. All its followers obligated to study, to know the content and obligated to obey or to do the messages in it because the Al-quran orders its followers own good character means the best refferencer for the good character can be seen in Al-quran. Every follower has to spend his/her time to study, to read, to master the messages in Al-qur’an so a wise follower in Islam religion in some one who can integrigate his/her all activities with Al-quran. Because of Al-quran stated only in Arabic language it need to translated in many languages in the world as in Indonesia and English so that the followers who can not master Arabic can understand what is said in Al-quran. So an English teacher who can integrate each mathery in the English curriculum to the Al-quran can be said a wise teacher, the wise teacher missed by all students no exception to the English teacher.